Quantitative assessment and clinical relevance of kallikrein-related peptidase 5 mRNA expression in advanced high-grade serous ovarian cancer - Gong, Weiwei; Liu, Yueyang; Seidl, Christof; Diamandis, Eleftherios P.; Kiechle, Marion; Drecoll, Enken; Kotzsch, Matthias; Magdolen, Viktor; Dorn, Julia (BMC cancer, 2019)
Background In ovarian cancer, dysregulation of mRNA expression of several components of the family of the kallikrein-related peptidases (KLKs) is observed. In this study, we have analyzed the KLK5 mRNA expression pattern in tumor tissue of patients suffering from high-grade serous ovarian cancer stage FIGO III/IV. Moreover, we have correlated the KLK5 mRNA levels with clinical outcome. Methods We assessed the mRNA expression levels of KLK5 in tumor tissue of 138 patients using quantitative PCR (qPCR). The mRNA levels were correlated with KLK5 antigen tumor tissue levels measured by ELISA (available for 41 of the 138 patients), established clinical features as well as patients’ outcome, using Chi-square-tests, Mann-Whitney U-tests and Spearman rank calculations as well as Cox regression models, Kaplan-Meier survival analysis and the log-rank test. Results A highly significant correlation between the mRNA expression levels and protein levels of KLK5 in tumor tissues was observed (r s = 0.683, p < 0.001). In univariate Cox regression analysis, elevated KLK5 mRNA expression was remarkably associated with reduced progression-free survival (PFS; p = 0.047), but not with overall survival (OS). Association of KLK5 mRNA expression with PFS was validated in silico using The Cancer Genome Atlas. For this, Affymetrix-based mRNA data ( n = 377) were analyzed applying the Kaplan-Meier Plotter tool ( p = 0.027). In multivariable Cox analysis, KLK5 mRNA values revealed a trend towards statistical significance for PFS ( p = 0.095), whereas residual tumor mass (0 mm vs. > 0 mm), but not ascites fluid volume (≤500 ml vs. > 500 ml), remained an independent indicator for both OS and PFS ( p < 0.001, p = 0.005, respectively). Conclusions These results obtained with a homogenous patient group with all patients suffering from advanced high-grade serous ovarian cancer support previous results suggesting elevated KLK5 mRNA levels as an unfavorable marker in ovarian cancer.